THE CONCEPT OF MORALITY AND VALUES EDUCATION IN ISLAMIC EDUCATION - Djafar, Chece; Kamaluddin, Munawir; Ondeng , Syarifuddin (Jurnal Kajian Pendidikan dan Psikologi, 2026)
This study aims to explore the relationship between the concept of morality in Islamic education and the implementation of value-based education within it. By understanding how these values are applied in the educational curriculum, it is expected to encourage the younger generation to develop good character and noble morals. Misunderstandings and poor implementation of moral education can lead to moral decline among youth, as reflected in various social issues, such as student brawls and other negative behaviors. Therefore, in Islamic education, an approach that integrates character education with religious teachings is considered essential. Inclusive teaching methods certainly require the development of strategies that can enhance students' moral and social awareness. Moreover, contributions from various parties, such as parents and the community, play a significant role in supporting this educational process. By integrating character education values into every subject, it is hoped that a learning atmosphere can be created that supports the holistic development of noble character. This study concludes with recommendations to enhance the practice of value-based education, including increasing parental and community involvement in supporting a positive educational environment for students.